Emotional self–other voice processing in schizophrenia and its relationship with hallucinations: ERP evidence. (5th May 2017) - Pinheiro, Ana P.; Rezaii, Neguine; Rauber, Andréia; Nestor, Paul G.; Spencer, Kevin M.; Niznikiewicz, Margaret
Abstract: Abnormalities in self–other voice processing have been observed in schizophrenia, and may underlie the experience of hallucinations. More recent studies demonstrated that these impairments are enhanced for speech stimuli with negative content. Nonetheless, few studies probed the temporal dynamics of self versus nonself speech processing in schizophrenia and, particularly, the impact of semantic valence on self–other voice discrimination. In the current study, we examined these questions, and additionally probed whether impairments in these processes are associated with the experience of hallucinations. Fifteen schizophrenia patients and 16 healthy controls listened to 420 prerecorded adjectives differing in voice identity (self‐generated [SGS] versus nonself speech [NSS]) and semantic valence (neutral, positive, and negative), while EEG data were recorded. The N1, P2, and late positive potential (LPP) ERP components were analyzed. ERP results revealed group differences in the interaction between voice identity and valence in the P2 and LPP components. Specifically, LPP amplitude was reduced in patients compared with healthy subjects for SGS and NSS with negative content. Further, auditory hallucinations severity was significantly predicted by LPP amplitude: the higher the SAPS "voices conversing" score, the larger the difference in LPP amplitude between negative and positive NSS. The absence of group differences in the N1 suggests that self–other voice processing abnormalities in schizophrenia are not primarily driven by disrupted sensory processing of voice acoustic information. The association between LPP amplitude and hallucination severity suggests that auditory hallucinations are associated with enhanced sustained attention to negative cues conveyed by a nonself voice.